2004
DOI: 10.1073/pnas.0305511101
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fitness costs for transgenicAedes aegyptiexpressing the GFP marker and transposase genes

Abstract: The development of transgenic mosquitoes that are refractory to the transmission of human diseases such as malaria, dengue, and yellow fever has received much interest due to the ability to transform a number of vector mosquito species with transposable elements. Transgenic strains of mosquitoes have been generated with molecular techniques that exhibit a reduced capacity to transmit pathogens. These advancements have led to questions regarding the fitness of transgenic mosquitoes and the ability of transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 23 publications
5
92
1
6
Order By: Relevance
“…Catteruccia et al (6) found that Anopheles stephensi homozygous transgenic lines have lower fitness compared with WT, and Irvin et al (7) reached similar conclusions with transgenic lines of Aedes aegypti. However, these studies could not distinguish fitness effects due to the transgene itself versus insertion-site effects and/or inbreeding depression (8).…”
supporting
confidence: 51%
“…Catteruccia et al (6) found that Anopheles stephensi homozygous transgenic lines have lower fitness compared with WT, and Irvin et al (7) reached similar conclusions with transgenic lines of Aedes aegypti. However, these studies could not distinguish fitness effects due to the transgene itself versus insertion-site effects and/or inbreeding depression (8).…”
supporting
confidence: 51%
“…aegypti was assessed using a life-table approach (Irvin et al 2004). From mosquitoes that had been in colony since 1961, three lines homozygous for the transgenes were established and maintained for 2-3 years.…”
Section: Research On Gmm Fitnessmentioning
confidence: 99%
“…Furthermore, the small size (1.3 kb) of the 3xP3-EGFP marker provides an additional advantage, as it allows small transposon constructs resulting in high transformation rates (Horn et al, 2002). This transformation system has been applied to generate transgenic insects in different orders as Diptera, Hymenoptera, Lepidoptera and Coleoptera (Horn et al,2002;Lorenzen et al, 2003;Robinson et al, 2004;Irvin et al, 2004). Among the Drosophila species, D. willistoni stands out for possessing a great genetic variability and ecological versatility, being one of most studied of the family Drosophilidae.…”
Section: Introductionmentioning
confidence: 99%
“…This transposon is naturally found in the genomes of some lepidopteran (Cary et al, 1989). The piggyBac element was first used to transform the medfly, C. capitata (Handler et al, 1998), and more recently it has been used for transformation of many other species (Horn and Wimmer, 2000;Handler and McColombs, 2000;Handler, 2001;Horn et al, 2002;Atkinson, 2002;Robinson et al, 2004;Irvin et al, 2004). Other important component for the effective development of insect transformation technology is the use of genetic markers that allows recognition of the transformed individuals (O'Brochta and Atkinson, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation